Kontribusi Penyuluh Agama Buddha dalam Meningkatkan Sikap Moderasi Beragama terhadap Generasi Muda di Desa Tegal Maja Kecamatan Tanjung Kabupaten Lombok Utara - Wati, Natia; Sentot; Firnadi, Aryanto (STAB Kertarajasa, 2024)
The purpose of this research is to understand and describe the religious moderation attitudes of the younger generation and the contribution of Buddhist religious instructors in enhancing these attitudes among the youth. This research uses a qualitative method with a descriptive-analytical approach. Data collection techniques include interviews, observations, and documentation. Data analysis involves three stages: data condensation, data presentation, and conclusion drawing and verification. The data sources for this research are primary data, obtained from interviews with informants such as Buddhist religious instructors and youth in Tegal Maja Village, and secondary data from journals, village documents, popular books, and social media related to the issue being studied. The results of this research indicate that the religious moderation attitude among the younger generation has been well-implemented. This is due to the significant contribution of Buddhist religious instructors, who have played a major role in enhancing religious moderation attitudes among the youth in Tegal Maja Village. This is evident in the improved attitudes of the younger generation, characterized by tolerance, mutual respect, and their non-involvement in acts of violence, radicalism, and intolerance.